The impact of surgery with general anesthesia on cognitive function and putamen volume: a cross-sectional study among older adults - Jiang, Jianjun; Zhang, Zhuyun; Zheng, Hong; Lu, Jian; Li, Wei (Frontiers in Aging Neuroscience, 2024)
BackgroundPrevious studies have shown that surgery under general anesthesia may diminish cognitive function; however, the proposed mechanisms need further elucidation. The purpose of the current study was twofold: (1) to compare overall and domain-specific differences in cognitive function between the surgery under general anesthesia group and the control group, and (2) to investigate the possible mechanisms of surgery under general anesthesia affecting cognitive function, using T1-structural magnetic resonance imaging.MethodsA total of 194 older adults were included in this study. Patients were divided into a surgery under general anesthesia group (n = 92) and a control group (n = 104). The two groups were matched for age, sex, and educational level. All participants underwent clinical evaluation, neuropsychological testing, blood biochemistry analysis, and T1 phase structural magnetic resonance imaging.ResultsWe found that older adults with a history of surgery under general anesthesia had lower Montreal Cognitive Assessment (MoCA) scores and smaller right putamen volumes (p < 0.05). Linear regression analysis (mediation model) indicated that surgery under general anesthesia affected MoCA scores by diminishing the volume of the right putamen (B = 1.360, p = 0.030).ConclusionWe found evidence that older adults who underwent surgery under general anesthesia had poorer cognitive function, which may have been caused by an apoptotic or otherwise toxic effect of anesthetic drugs on the volume of the right putamen.